Lutathera® Orphans: State of the Art and Future Application of Radioligand Therapy with 177Lu-DOTATATE - Luca Urso; Alberto Nieri; Licia Uccelli; Angelo Castello; Paolo Artioli; Corrado Cittanti; Maria Cristina Marzola; Luigia Florimonte; Massimo Castellani; Sergio Bissoli; Francesca Porto; Alessandra Boschi; et al. (MDPI AG, 2023)
Lutathera® is the first EMA- and FDA-approved radiopharmaceutical for radioligand therapy (RLT). Currently, on the legacy of the NETTER1 trial, only adult patients with progressive unresectable somatostatin receptor (SSTR) positive gastroenteropancreatic (GEP) neuroendocrine neoplasms (NET) can be treated with Lutathera®. Conversely, patients with SSTR-positive disease arising from outside the gastroenteric region do not currently have access to Lutathera® treatment despite several papers in the literature reporting the effectiveness and safety of RLT in these settings. Moreover, patients with well-differentiated G3 GEP-NET are also still "Lutathera orphans", and retreatment with RLT in patients with disease relapse is currently not approved. The aim of this critical review is to summarize current literature evidence assessing the role of Lutathera® outside the approved indications. Moreover, ongoing clinical trials evaluating new possible applications of Lutathera® will be considered and discussed to provide an updated picture of future investigations.